Pelatihan Penulisan Artikel Ilmiah bagi Guru Program Studi Perbankan Syariah di SMK Negeri 1 Kudus - Moh. Nurul Qomar; Ulfah Mey Lida; Sufiana Noor (Inspirasi Nusantara, 2022)
Along with the development of science and technology, the demands of the government and society on teacher professionalism are increasing. One form of writing that can be produced by teachers to fulfill Continuing Professional Development (PKB) is scientific articles. The purpose of this activity is to provide an in-depth and comprehensive understanding of scientific articles, including the basic concepts of scientific writing, research methodologies, and journal style so that teachers gain broader insight into scientific articles and journals that can publish scientific articles. The methods that will be used in this service activity include classical and individual approaches. The scientific article writing training for Islamic Banking teachers was carried out for 15 days, namely November 1-15 2021. During those fifteen days, participants were accompanied synchronously and asynchronously by the PKM team. Scientific article writing training for Islamic Banking teachers at SMK N 1 Kudus is very useful. Participants who initially were unfamiliar with scientific articles, became knowledgeable and had experience in this field